Assessing provider performance of intrapartum care using simulated encounters and clinical vignettes: A comparison study from Tanzania. Issue 1 (15th October 2021) - Young, Anna Marie P.; Marx, Melissa A.; Frost, Emily; Hazel, Elizabeth; Kabanywanyi, Abdunoor M.; Mohan, Diwakar
Abstract: Objective: To compare clinical vignettes and objective structured clinical examinations (OSCE) as methods for assessing the quality of intrapartum care among skilled providers in rural primary‐level health facilities in Tanzania. Methods: Cross‐sectional study conducted at six health facilities in the Simiyu region of Tanzania. Providers were assessed using OSCE and clinical vignettes in spontaneous delivery, neonatal resuscitation, and management of postpartum hemorrhage. Trained researchers used a structured clinical checklist. The frequencies of items are presented as percentages and the agreement of the methods of assessment are reported using kappa statistics (high: kappa > 0.80, moderate: kappa = 0.60–0.80, low: kappa < 0.60). Results: Most healthcare providers were female (60.7%), registered nurses by training (29.0%), and worked in a dispensary (56.1%), with an average age of 33 years and an average of 7.4 years of experience in their respective professions. Five items had high agreement between OSCE and clinical vignettes: postpartum vital signs every 15 min, oxytocin within 1 min of birth, diagnosis of postpartum hemorrhage, elevating legs of the mother, and deciding on manual compression of the uterus. Conclusion: OSCE and clinical vignettes should be viewed as complimentary to one another in the assessment of provider knowledge and skill, with priority given to OSCE, particularly in intrapartum care. Abstract : Clinical vignettes and objective structured clinical examinations are complimentary methods of assessment of intrapartum care in Tanzania, with priority given to objective structured clinical examinations.